2019
DOI: 10.5005/jp-journals-10005-1698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CRAFT as a Tool for Caries Risk Assessment in 3- to 6-year-old Children and its Validation against Alban's Test: A Pilot Study

Abstract: Introduction:Dental caries is a multifactorial disease and a dynamic process that can be prevented and reversed during the early stage. Risk assessment is an important step in decision-making and treatment planning. There are no valid tools available for the Indian population. Caries risk assessment for treatment (CRAFT) is a chairside tool for caries risk assessment and management. Valid, reliable, economical, and chairside caries risk assessment tool is the need of the hour for general and pediatric dentists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, the apps have to be informed by health professionals, with good design detail, grounded and validated for use, as the Canadian CRA tool has been (33,34). Although there have been numerous studies that have investigated caries risk factors and the predictive validity of CRA tools, this paper appears to be the first to report on the qualitative analysis of feedback acquired through pilot testing of a CRA tool indicated for use by non-dental primary health care providers (9,25,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). A similar British study has reported on feedback from the pilot testing of an online integrated oral health and risk assessment tool (DEPPA).…”
Section: Discussionmentioning
confidence: 99%
“…However, the apps have to be informed by health professionals, with good design detail, grounded and validated for use, as the Canadian CRA tool has been (33,34). Although there have been numerous studies that have investigated caries risk factors and the predictive validity of CRA tools, this paper appears to be the first to report on the qualitative analysis of feedback acquired through pilot testing of a CRA tool indicated for use by non-dental primary health care providers (9,25,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). A similar British study has reported on feedback from the pilot testing of an online integrated oral health and risk assessment tool (DEPPA).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted by Thakur et al reported a high correlation between CRAFT and Alban scores (Spearman's Rho = 0.874; p < 0.001), discounting the need for microbial testing. 7 …”
Section: Discussionmentioning
confidence: 99%
“…About 46% 23 of the participants reported High CRAFT scores, 40% 20 had Moderate, and 14 % 7 had Low CRAFT scores. About 34% 17 of the participants reported maximum ECOHIS score of 6 whereas 4% 2 had the lowest ECOHIS score of 1.…”
Section: R Esultsmentioning
confidence: 97%
“…All the parameters analyzed in this study, OHRQoL, caries risk, and dental status, were evaluated using indices and applications sourced from existing literature evidence [ 9 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Caries risk assessment (CRA) is a pivotal tool for predicting future caries and helps in guiding evidence-based clinical decisions [ 8 ]. In this pursuit, the caries risk assessment for treatment (CRAFT) tool emerges as an indigenous, interview-based tool developed for ascertaining caries risk in children that primarily focuses on dietary habits, fluoride exposure, decay, and related factors reported by parents [ 9 ].…”
Section: Introductionmentioning
confidence: 99%